Back Cover: Kamlet–Taft Solvation Parameters of Solvate Ionic Liquids (ChemPhysChem 19/2016). Issue 19 (4th October 2016) - Dolan, Dr Andrew; Sherman, Dylan A.; Atkin, Rob; Warr, Gregory G.
Abstract : The Back Cover picture represents the H‐bond‐like Lewis acidity of lithium solvate ionic liquids as probed by dicyano bis(1‐benzyl‐1‐(2‐pyridyl)‐N‐(3, 4‐dimethyl)phenyl‐methanimine) ferrate(II) (Burgess' Dye). More information can be found in the Full Paper by G. G. Warr and co‐workers onpage 3096 in Issue 19, 2016 (DOI:10.1002/cphc.201600361 ).